Endoscopic ultrasound-guided liver biopsy: a multicenter experience - Diehl, David L.; Johal, Amitpal S.; Khara, Harshit S.; Stavropoulos, Stavros N.; Al-Haddad, Mohammed; Ramesh, Jayapal; Varadarajulu, Shyam; Aslanian, Harry; Gordon, Stuart R.; Shieh, Frederick K.; Pineda-Bonilla, Jonh J.; Dunkelberger, Theresa; Gondim, Dibson D.; Chen, Eric Z. (Endoscopy International Open, 2015)
Background and aims: Endoscopic ultrasound-guided (EUS) liver biopsy (LB) is proposed as a newer method that offers several advantages over existing techniques for sampling liver tissue. This study evaluated the diagnostic yield of EUS-LB as the primary outcome measure. In addition, the safety of the technique in a large patient cohort was assessed. Patients and methods: Patients undergoing EUS for evaluation of elevated liver enzymes or hepatic disease were included in this prospective, non-randomized, multicenter study. EUS-LB was performed with EUS-fine needle aspiration (FNA; 19-gauge needle). Tissue was formalin-fixed and stained with hematoxylin and eosin, and trichrome. Using a microscope micrometer, specimen length was measured and the number of complete portal triads (CPTs) were counted. The main outcome measure was to assess the diagnostic yield of EUS-LB, and to monitor for any procedure-related complications. Results: Patients (110; median age, 53 years; 62 women) underwent EUS-LB at eight centers. The indication was abnormal liver enzymes in 96 patients. LB specimens sufficient for pathological diagnosis were obtained in 108 of 110 patients (98 %). The overall tissue yield from 110 patients was a median aggregate length of 38 mm (range, 0 – 203), with median of 14 CPTs (range, 0 – 68). There was no statistical difference in the yield between bilobar, left lobe only, or right lobe only biopsies. There was one complication (0.9 %) where self-limited bleeding occurred in a coagulopathic and thrombocytopenic patient. This complication was managed conservatively.Conclusions: EUS-guided LB was a safe technique that yields tissue adequate for diagnosis among 98 % of patients evaluated.